Assessment of LNAPL transmissivity for contaminated sites characterization in São Paulo state - Garcia, Marcos Vinícius Corrêa; Leite, Ellen Caroline Puglia; Pede, Marco Aurelio Zequim [UNESP]; Shinzato, Mirian Chieko; Freitas, Juliana Gardenalli (FapUNIFESP (SciELO), 2021)
Light non-aqueous phase liquids (LNAPL), such as liquid fuels, are present in many contaminated sites. To adequately manage these sites, it is important to know the product mobility, to support decisions on remediation systems and risk assessment. One alternative to quantify mobility is to quantify the LNAPL transmissivity, which is rarely applied in Brazil. This work aimed to evaluate the applicability of this parameter in LNAPL contaminated sites with different conditions. Tests were performed in three sites, with different lithologies, types of contaminants and contamination histories. In some tests, it was not possible to obtain representative values of LNAPL transmissivity due to fluids levels instability, caused by pumping systems and precipitation events, and operational problems during the tests. Despite being a simple test, in some cases, the determination of LNAPL transmissivity may not be feasible, especially for low mobility LNAPLs, that require long period tests. The main factors controlling LNAPL transmissivity values were lithology, position of the well in the plume, and water level elevation in relation to the historical series. Thus, LNAPL transmissivity can be a useful parameter in the management of contaminated sites, but its interpretation must be made cautiously and integrated with other site data.
Avaliação do parâmetro transmissividade de LNAPLs para caracterização de áreas contaminadas no estado de São Paulo
Keywords: free phase; groundwater; mobility; monitoring; organic contaminants